1999
DOI: 10.1046/j.1439-0450.1999.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Selective Media for Bifidobacteria in Poultry and Rabbit Caecal Samples

Abstract: Five media were evaluated to determine their selectivity for Bifidobacterium sp. in hen and rabbit caecal samples. The colonies arising on the plates inoculated with the caecal samples were Gram stained and screened for the presence of fructose-6-phosphate phosphoketolase activity. Rogosa agar modified by the addition of cysteine-hydrochloride (0.05 % w/v), Beeren's agar (with 5 ml/l of propionic acid as a selective agent), BS 2 agar (containing per one litre sodium propionate 15 g, lithium chloride 3 g, parom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 7 publications
(8 reference statements)
1
30
0
Order By: Relevance
“…Fairchild et al (2001) and Spring et al (2000) reported that the use of probiotics in the ration reduces the total population of E. coli forms in the intestinal lumen. Rada et al (1999) found that the use of Lactobacillus salivary in the chicken's diet can reduce the coliform bacteria population significantly as compared with the control treatment by reducing the intestinal pH level. Chung and Day (2004) showed that lactose in dried whey cannot be digested or absorbed so fermented by lactic acid bacteria, production of lactic acid and reduction in the pH and multiplication of pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 97%
“…Fairchild et al (2001) and Spring et al (2000) reported that the use of probiotics in the ration reduces the total population of E. coli forms in the intestinal lumen. Rada et al (1999) found that the use of Lactobacillus salivary in the chicken's diet can reduce the coliform bacteria population significantly as compared with the control treatment by reducing the intestinal pH level. Chung and Day (2004) showed that lactose in dried whey cannot be digested or absorbed so fermented by lactic acid bacteria, production of lactic acid and reduction in the pH and multiplication of pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 97%
“…The antibiotic mupirocin was previously found to effectively select for bifidobacteria from other bacteria typically found in GIT and fecal samples (31,(34)(35)(36). The addition of mupirocin to mMRS has not been reported for the selective isolation of bifidobacteria but, along with the culture conditions used in the present study, appeared to be selective for all Bifidobacterium strains tested.…”
Section: Discussionmentioning
confidence: 99%
“…Bifidobacteria have been cultured from the cecal contents of chickens (31,35,51), rats (43), rabbits (20,35,46), pigs (37), and humans (21). Isolates were confirmed as belonging to the genus Bifidobacterium in all but the rat and pig studies, through the detection of fructose-6-phosphate phosphoketolase (F-6-PPK) (41).…”
mentioning
confidence: 99%
“…One gram of the composite excreta sample from each cage was diluted with 9 ml of 1% peptone broth (Becton, Dickinson and Co., Franklin Lakes, NJ) and then homogenised. Viable counts of bacteria in the caecal and ileal samples were then conducted by plating serial 10-fold dilutions (in 1% peptone solution) onto lactobacilli medium III agar plates (Medium 638; DSMZ, Braunschweig, Germany), MacConkey agar plates (Difco Laboratories, Detroit, MI), Perfringens agar base (Perfringens TSC Agar; Oxoid, Basingstoke, UK) and WilkinsChalgren agar (Oxoid, Nepean, Ontario, Canada) supplemented with glacial acetic acid (1 ml/l) and mupirocin (100 mg/l) extracted from antimicrobial discs (Oxoid; Rada et al 1999) to isolate the Lactobacillus, Escherichia coli, Clostridium perfringens and Bifidobacteria, respectively. The lactobacilli medium III agar plates were then incubated for 48 h at 37 °C under anaerobic conditions.…”
Section: Methodsmentioning
confidence: 99%